2007
DOI: 10.1055/s-2007-990838
|View full text |Cite
|
Sign up to set email alerts
|

[RuCl3(H2O)n]-Catalyzed Direct Arylations with Bromides as Electrophiles

Abstract: Catalytic amounts of [RuCl 3 (H 2 O) n ] allow for direct arylations via C-H bond functionalization with aryl bromides, bearing a variety of important functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 8 publications
0
64
0
2
Order By: Relevance
“…Ackermann et al reported one-pot synthesis of highly regioselective indoles 94 via TiCl 4 -catalyzed hydroamination and a 5-endo Heck cyclization, starting from 2-chloroaniline 92 and alkynes (Scheme 21) [63]. The authors later reported the same transformation with Ru 3 (CO) 12 catalyst [64].…”
Section: Reactions Triggered By Intermolecular Hydroaminationmentioning
confidence: 97%
“…Ackermann et al reported one-pot synthesis of highly regioselective indoles 94 via TiCl 4 -catalyzed hydroamination and a 5-endo Heck cyclization, starting from 2-chloroaniline 92 and alkynes (Scheme 21) [63]. The authors later reported the same transformation with Ru 3 (CO) 12 catalyst [64].…”
Section: Reactions Triggered By Intermolecular Hydroaminationmentioning
confidence: 97%
“…Hence, palladium[17e21] and copper [17,22] complexes were found to enable the formation of indoles bearing inter alia aryl-, alkyl-or alkoxycarbonyl-substituents on nitrogen. [7] In continuation of our research program on sustainable catalysis for effective heterocycle syntheses, [23] we became interested in exploring the unprecedented use of inexpensive nickel catalysts [24] for a modular indole synthesis starting from ortho-alkynylhaloarenes 1, the results of which we wish to disclose herein.…”
Section: Introductionmentioning
confidence: 99%
“…[18] However, aryl chlorides are arguably the most useful single class of halides due to their lower cost and the wider diversity of (commercially) available compounds. [19,20] As part of our program on the use of more easily accessible and less expensive electrophiles, such as chlorides [21][22][23] and tosylates, [24] in direct arylation reactions, [25,26] we became interested in probing palladium-catalyzed direct arylations of 1,2,3-triazoles with aryl chlorides. [27] A very recent report by Oshima and co-workers on a nonthermal microwave effect on palladium-catalyzed direct arylations of 1,2,3-triazoles with aryl chlorides, [28] prompted us to disclose our own results on the direct arylations of 1,2,3-triazoles with aryl chlorides through conventional heating.…”
Section: Introductionmentioning
confidence: 99%